The Effect of Eight Weeks of Core Stability Training and Chitosan Supplementation on Cholecystokinin (CCK) and Peptide YY (PYY) Levels in Overweight Women: A Randomized Controlled Trial - Nasim Rahimi; Saeid Shamlou Kazemi; Ali Hemati Afif; Aida Baghbani (Journal of Mazandaran University of Medical Sciences)
Background and purpose: Obesity disrupts the secretion of appetite-regulating hormones, such as peptide YY (PYY) and cholecystokinin (CCK), which disrupts natural appetite control mechanisms and promotes excessive food intake and weight gain. Over time, these disturbances elevate the risk of metabolic disorders. This study aimed to investigate the effects of eight weeks of core stability training combined with chitosan supplementation on anthropometric indices, lipid profiles, and gastrointestinal hormones (CCK and PYY) in obese women. Materials and methods: This clinical trial was conducted on 60 obese women (BMI: 30.83±1.43), who were randomly assigned to three intervention groups and one control group. Participants in the exercise-only group performed core stability training three times per week for eight weeks. The supplement-only group consumed two 500 mg chitosan capsules daily for the same duration. The combined intervention group simultaneously engaged in both the exercise protocol and chitosan supplementation. Measurements of study variables were taken twice before and after the intervention. Data analysis was performed using two-way ANOVA in SPSS (version 27) with a significance level of α = 0.05. Results: The findings revealed significant differences in PYY and CCK levels among the intervention groups (exercise, supplement, and combined intervention) (P< 0.05), whereas no significant changes were observed in the control group (P> 0.05). Additionally, the intervention groups demonstrated significant improvements in anthropometric indices and lipid profiles (P< 0.05). Conclusion: Core stability training, chitosan supplementation, and their combined implementation positively influenced anthropometric measures, plasma lipid profiles, and gastrointestinal hormones (PYY and CCK). These findings suggest that combining exercise with supplementation may be an effective strategy for improving metabolic health and supporting weight management in obese women.